Pengaruh Media Komik Digital Terhadap Minat dan Hasil Belajar Siswa Pada Pelajaran IPA Sekolah Dasar - Rahmah, Nur; Khairunnisa, Khairunnisa; M. Gagaramusu, Yusdin; Aprilia, Anisa (Jurnal Didaktika Pendidikan Dasar, 2025)
This study aims to examine the effect of using digital comic media on students’ interest in learning and learning outcomes in science lessons in grade V elementary school. This study used a mixed method approach with a sequential explanatory strategy. The research subjects consisted of fifth grade students at SDN 3 Palu. In the first stage, quantitative data was collected through tests and questionnaires to measure students’ learning interest and learning outcomes. The second stage involved collecting qualitative data through classroom observations and interviews to explore students’ experiences in using digital comics as learning media. Quantitative data analysis showed the positive effect of using digital comics on students’ interest in learning, which was classified as very high. Further qualitative analysis revealed that students felt more involved and active in the learning process, and gained a better understanding of the science subject matter through digital comics. These findings indicate that digital comics media can improve students interest and learning outcomes in an interesting and fun way. This research suggests developing the use of comic-based digital media for a more participatory and student-oriented learning approach.